Changes in the gut microbiota of patients with sarcopenia based on 16S rRNA gene sequencing: a systematic review and meta-analysis - Song, Qi; Zhu, Youkang; Liu, Xiao; Liu, Hai; Zhao, Xinyi; Xue, Liyun; Yang, Shaoying; Wang, Yujia; Liu, Xifang (Frontiers in Nutrition, 2024)
Sarcopenia, an age-related disease, has become a major public health concern, threatening muscle health and daily functioning in older adults around the world. Changes in the gut microbiota can affect skeletal muscle metabolism, but the exact association is unclear. The richness of gut microbiota refers to the number of different species in a sample, while diversity not only considers the number of species but also the evenness of their abundances. Alpha diversity is a comprehensive metric that measures both the number of different species (richness) and the evenness of their abundances, thereby providing a thorough understanding of the species composition and structure of a community. This meta-analysis explored the differences in intestinal microbiota diversity and richness between populations with sarcopenia and non-sarcopenia based on 16s rRNA gene sequencing and identified new targets for the prevention and treatment of sarcopenia. PubMed, Embase, Web of Science, and Google Scholar databases were searched for cross-sectional studies on the differences in gut microbiota between sarcopenia and non-sarcopenia published from 1995 to September 2023 scale and funnel plot analysis assessed the risk of bias, and performed a meta-